Purchasing power parity in African countries: evidence from panel SURADF test - Baharumshah, Ahmad Zubaidi; Lau, Evan; Nziramasanga, Mudziviri T. (Blackwell Publishing, 2010)
This study reexamines the validity of long-run purchasing power parity (PPP) hypothesis using a battery of panel unit root tests for 11 developing countries in Africa over the period 1980-2007. Based on the conventional panel unit root tests, we found evidence that the monthly real exchange rates in these countries were mean reverting. By contrast, the series-specific unit root test proposed by Breuer et al. (SURADF) reveals that only six of the 11 RERs series were stationary using the US dollar as reference currency. Additionally, our results reveal that there is stronger evidence of the parity condition with the Rand-based rates than in the other currency-based rates like the US dollar or Euro.We conclude that PPP holds in some, but not all, of the African countries according to the SURADF tests.